Triply responsive soft matter nanoparticles based on poly[oligo(ethylene glycol) methyl ether methacrylate-block-3-phenylpropyl methacrylate] copolymers - Pei, Y.; Jarrett, K.; Saunders, M.; Roth, P.; Buckley, C.; Lowe, Andrew (R S C Publications, 2016)
The stimulus-responsive properties of soft matter nanoparticles based on poly[oligo(ethylene glycol) methyl ether methacrylate-block-3-phenylpropyl methacrylate] (p(OEGMA-block-PPMA)) copolymers in methanol and ethanol are described. Methanolic synthesis, with 4-cyanopentanoic acid dithiobenzoate as the RAFT mediating agent, facilitates simple access to nanoparticles exhibiting the full range of common morphologies (spheres, worms and vesicles) simply by varying the copolymer composition (fixed average degree of polymerization (X¯n) of the pOEGMA macro-CTA for variable X¯n of the pPPMA block). Interestingly, we demonstrate that p(OEGMAx-block-PPMAy) nanoparticles are able to elicit three types of response to externally applied stimuli. These materials possess two distinct, but complementary, reversible thermal responses-one that results in an order-order transition, i.e. a morphological change, while the second is a reversible order-disorder transition based on upper critical solution temperature (UCST)-type behaviour associated with the pOEGMA coronal chains in the nanoparticles. Finally, we report the first example where specific p(OEGMA-block-PPMA) nanoparticles are shown to be sensitive to addition of an organobase-a response that is accompanied by an order-order, worm-to-sphere, morphology transition.